Flow Cytometry-Assessed PD1/PDL1 Status in Tumor-Infiltrating Lymphocytes: A Link With the Prognosis of Diffuse Large B-Cell Lymphoma - Chen, Zihang; Deng, Xueqin; Ye, Yunxia; Zhang, Wenyan; Liu, Weiping; Zhao, Sha (Frontiers in Oncology, 2021)
The PD1/PDL1 status of tumor-infiltrating lymphocytes (TILs) in diffuse large B-cell lymphoma (DLBCL) reflects immune function. However, the previously reported methods for evaluating this status are complex and may not be widely used in clinical practice. In addition, these studies did not introduce healthy controls to designate the cut-off when evaluating the prognostic value of the status. In this study, we retrospectively evaluated the PD1/PDL1 status in TILs of 24 DLBCL tissue samples and normal immune cells in 61 demographically matched healthy controls (tissue samples from patients with reactive hyperplasia [RH]) by flow cytometry. We investigated the prognostic value of the PD1/PDL1 status in TILs by precisely determining the cut-off value and assessing the reliability of flow cytometry. The mean fluorescence intensity (MFI) of PD1 in TIL-T-cells (TIL-Ts; median, 110) and CD8+TIL-Ts (median, 64) was significantly higher than that of CD3+T-cells (median, 64) and CD8+ T-cells (median, 34) in RH. The cut-off values of PD1/PDL1 status for analyzing prognostic values were defined considering the PD1/PDL1 status of samples from both patients with DLBCL and healthy controls. High MFI of PD1 in TIL-Ts (MFI >108, P = 0.022), high proportion of PD1+CD4+TIL-Ts (>1.1% of CD4+TIL-Ts, P = 0.049), high proportion of PD1+CD8+TIL-Ts (>2% of CD8+TIL-Ts, P = 0.025), and high MFI of PDL1 in TIL-Ts (MFI >83, P = 0.023) were risk factors for inferior prognosis of DLBCL. Our results indicate that flow cytometry is a reliable and convenient method for evaluating the immune-checkpoint status of TILs, which probably holds major implications in clinical practice.